Interventional radiology for post-gastrectomy complications - Suyoung Park; Ji Hoon Shin; Kichang Han (Society of Gastrointestinal Intervention, 2019)
Complications following gastrectomy can be life-threatening, but, they are commonly managed by interventional radiology. This review describes possible complications after gastrectomy by dividing them into vascular and non-vascular categories. Vascular complications are mostly arterial bleeding and varix bleeding. Non-vascular complications comprise abscess, fistula, benign anastomotic stricture, and malignant obstruction, e.g. afferent loop syndrome, by tumor recurrence. Interventional managements for treatment of post-gastrectomy complications are safe, effective, and less invasive compared with surgery.